Prevalence of Hypercalcaemia in a Renal Transplant Population: A Single Centre Study. (14th July 2016) - Amin, Tony; Coates, P. Toby; Barbara, Jeffrey; Hakendorf, Paul; Karim, Nazmul
Abstract : Introduction . Postrenal transplant bone disease is a significant problem. Factors influencing postrenal transplant bone status include high dose acute and low dose long-term steroid use, persistent hypercalcaemia, and graft failure. In this study, we aimed to determine the prevalence of hypercalcaemia and to evaluate the risk factors for postrenal transplant hypercalcaemia in long-term renal transplant patients at our centre. Methods . This is a biochemical audit in which we studied renal transplant recipients from the Central Northern Adelaide Renal Transplant Services, South Australia. Inclusion criteria include kidney transplant patients with functioning graft since 1971 and at least 3 months after transplantation at the time of analysis. Hypercalcaemia was defined as persistently elevated serum corrected calcium greater than or equal to 2.56 mmol/L for three consecutive months. Results . 679 renal transplant recipients with a functioning graft were studied and 101 were hypercalcaemic between March 2011 and June 2011 (15%). 60% of the hypercalcaemic patients were male and 40% were female, with chronic glomerulonephritis (39%) being the commonest cause of their end stage kidney disease (ESKD). Prevalence was similar in those that had haemodialysis and peritoneal dialysis pretransplantation. Hypercalcaemia in the renal transplant population was not secondary to suboptimal allograft function but secondary to pretransplantation hyperparathyroidism with persistent high parathyroid hormone (PTH) levels after transplantation. Conclusion . There is a high prevalence of hypercalcaemia (15%) in renal transplant recipients. The predominant cause for hypercalcaemia is pretransplantation hyperparathyroidism. The magnitude of pretransplantation hyperparathyroidism is the major determinant for long-term parathyroid function rather than graft function or pretransplantation duration on dialysis or mode of dialysis.